PERINATAL TOPOGRAPHY OF THE CAROTID ARTERIES - Герасим, Л.М. (World of Medicine and Biology, 2014)
The objective of the work is to find out topographic-anatomical peculiarities of the general carotid arteries in fetuses and human neonates. The research is conducted on 57 preparations of dead fetuses (from 4 to 10 months) and 8 neonates (5 isolated organocomplexes in particular) without external signs of anatomical defects or abnormalities and without evident macroscopic deviations from the normal structure of the cardio-vascular system. Up-to-date and adequate morphological methods of examination are used: macro- and microscopy, arterial injection with the mixture on the basis of red lead with further dissection and radiography, preparing topographic-anatomical cuts in three inter-perpendicular surfaces. In the perinatal period of human ontogenesis the general carotid artery is found to be divided into the external and internal carotid arteries on the level of the hyoid bone in 48% of early fetuses (4-5 months) and 75% - in late fetuses (8-10 months) and newborns. In 28% (for early fetuses) and 16% (for late fetuses and newborns) the general carotid artery is divided on the level of the superior margin of the thyroid gland (descending division), and in 24% of early fetuses and 8% of late fetuses and neonates this division is found higher the hyoid bone (ascending division). Projection of the external carotid artery within the borders of the carotid triangle is detected along the midline passing through the point in the place of crossing of the lateral margin of the omohyoid muscle with the anterior margin of the sternocleidomastoid muscle, forming an acute angle (15-30°) with the latter one. With the age of fetuses this angle becomes larger. During perinatal period bifurcation of the general carotid artery is skeletotopically shifted caudally on one cervical vertebra. Division of the general carotid artery into the external and internal one is detected by two shapes: parallel and bulbar. A parallel shape of the carotid artery division is the form of bifurcation when the external and internal carotid arteries pass parallel to each other and touching one another, the angle of division is approximately 10-20°. A bulbous shape of the carotid artery division means its division at a blunt angle with further approaching of these arteries one to another forming a bulb-like shape. A parallel shape of the external carotid artery division is typical, as it constitutes 84% of cases found in fetuses and neonates, a bulbar shape is a variant (16%). In front of the place of bifurcation of the general carotid artery in the perinatal human ontogenesis in 78% of cases the upper laryngeal nerve passes, in other cases (22%) it passes more cranially from the point of division of the external carotid artery on 0,3-0,5 cm anterior from the external and internal carotid arteries. This topographic-anatomical location should be considered during surgery in the cervical region in newborns and infants.
Keywords: general carotid artery; topography; perinatal period